The role of professional training of future teachers to implement the integrative approach in the education of Kazakhstani elementary schoolchildren - Найманова, Динара; Лебедева, Лариса (Pedagogy and Psychology, 2022)
The article presents the significance of professional training of students for the application of the integrative approach to teaching in the elementary grades in schools of Kazakhstan. Examples of exercises and techniques that can be used to design an integrative lesson are offered. The syllabus of a higher education course does not always clearly reflect the topics of how to conduct practical lessons on designing a lesson using the integrative approach. And to optimize the teaching skills of students should be through the use of technology that systematically contribute to the improvement of practical skills of students. The problem of the research is that future teachers, passing the internship in the school are not always able to apply the integrative methodology correctly. Students need to present the theoretical and practical aspects of this methodology in connection with its extended application in the process of teaching in the primary level and have effective learning outcomes already at the beginning of their teaching career. The future elementary teacher must have the skills to teach the methods of various disciplines and be able to integrate them. For the research work, primary education curricula, educational-methodical complexes, lectures and dissertations on the subject of integrating primary level subjects were used. The work was conducted in the higher educational institution of Almaty - Kazakh National University named after Abay. According to the review of the research, the necessity of introducing the course of designing integrative lessons in the elementary school has a sufficient grounding in the system of students’ training of all the courses of the pedagogical specialty. Keywords: integrative approach; practical skills; syllabus; learning content; pedagogical process; innovative methods; clip thinking.